2000
DOI: 10.1210/en.141.4.1366
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-fos Expression in Hypothalamic Nuclei by  - and  -Receptor Agonists: Correlation with Catecholaminergic Activity in the Hypothalamic Paraventricular Nucleus

Abstract: Administration of the preferential mu-opioid receptor agonist, morphine, and selective K-opioid receptor agonists elicits activation of the hypothalamus-pituitary-adrenocortical axis, although the site or the molecular mechanisms for these effects have not been determined. The expression ofFos, the protein product of the c-fos protooncogene, has been widely used as an anatomical marker of monitoring neuronal activity. In the present study we evaluated 1) the effects of the mu-opioid receptor agonist, morphine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 0 publications
5
43
0
Order By: Relevance
“…Dynorphin, which plays a role in regulating the stress response, is colocalized with CRF in the paraventricular nucleus of the hypothalamus (Roth et al, 1983) and has been found to modulate the effects of CRF on autonomic function (Overton and Fisher, 1989). Agonists also increase CRF release (Buckingham and Cooper, 1986) and stimulate the hypothalamic-pituitary-adrenal axis (Ur et al, 1997;Laorden et al, 2000). In light of these findings, it seems possible that priming with spiradoline in our study led to downstream activation of brain CRF 1 systems involved in the regulation of stress.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Dynorphin, which plays a role in regulating the stress response, is colocalized with CRF in the paraventricular nucleus of the hypothalamus (Roth et al, 1983) and has been found to modulate the effects of CRF on autonomic function (Overton and Fisher, 1989). Agonists also increase CRF release (Buckingham and Cooper, 1986) and stimulate the hypothalamic-pituitary-adrenal axis (Ur et al, 1997;Laorden et al, 2000). In light of these findings, it seems possible that priming with spiradoline in our study led to downstream activation of brain CRF 1 systems involved in the regulation of stress.…”
Section: Discussionmentioning
confidence: 52%
“…Opioids have been shown to enhance NE turnover in the paraventricular nucleus of the hypothalamus (Laorden et al, 2000), increase NE metabolism in the brain stem and cortex (Kunihara et al, 1992), and stimulate NE release in the hippocampus (Jackisch et al, 1986). In addition, the NE transport inhibitor, imipramine, enhances spiradoline-induced analgesia (Kunihara et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cocaine does not induced c-fos expression in this area (Torres and Rivier, 1994;Chang et al, 1995). whereas cannabinoids, opioids, alcohol and nicotine do (Chang et al, 1995;Valentine et al, 1996;Matta et al, 1997;Wenger et al, 1997;Laorden et al, 2000), although there is only evidence for c-fos expression in CRF+ neurons in the case of nicotine (Matta et al, 1997).…”
Section: Introductionmentioning
confidence: 90%
“…NA and its metabolite in the central nervous system, 3-methoxy-4-hydroxyphenylethylen glycol (MHPG), were determined by high-performance liquid chromatography (HPLC) with electrochemical detection as described previously (Laorden et al, 2000a). Bilateral tissue samples of the PVN were dissected according to the technique of Palkovits (1973), weighed, placed in perchloric acid (0.1 M), homogenized, and centrifuged, and the supernatants were taken for analysis and filtered through 0.22-m GV filter (Millipore Corporation).…”
Section: Crf1 Receptor and Morphine Withdrawal 865mentioning
confidence: 99%